The Influence of Transformational Leadership and Work Motivation on Job Satisfaction (Literature Review Study) - Ramdhani, Rija; Cahaya, Yohanes Ferry (Dinasti Publisher, 2025)
Previous research or relevant research is very important in a research or scientific article that serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews the influence of transformational leadership and work motivation on job satisfaction. Work motivation and transformational leadership style are closely related to employee job satisfaction because they are driving factors that create work enthusiasm in humans to work together, efficiently and integrated. This study uses a qualitative descriptive method. The results of the study indicate that transformational leadership and work motivation have an effect on job satisfaction. Transformational leadership has a significant positive effect on employee job satisfaction. Work motivation has a positive and significant effect on job satisfaction. The aim is to determine the effect of transformational leadership style and work motivation on employee job satisfaction.